American Business Law, Volume I/American Business Law, Volume II (Book). - Winter, Sidney G.; Hills, Elmer W. (The Accounting Review, 1944)
Abstract Reviews two books on business law. "American Business Law," vol. 1, by W.R. MacMillan; "American Business Law," vol. 2, by V. Winters Hoerr and Raymond J. Goss.